2017
DOI: 10.1021/jacs.7b10316
|View full text |Cite
|
Sign up to set email alerts
|

Opening the Cages of Faujasite-Type Zeolite

Abstract: Zeolites are widely used in industrial processes, mostly as catalysts or adsorbents. Increasing their micropore volume could further improve their already exceptional catalytic and separation performances. We report a tunable extraction of zeolite framework cations (Si, Al) on a faujasite-type zeolite, the archetype of molecular sieves with cages and the most widely used as a catalyst and sorbent; this results in ca. 10% higher micropore volume with limited impact on its thermal stability. This increased micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
143
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(151 citation statements)
references
References 24 publications
7
143
1
Order By: Relevance
“…In order to understand the changes at the molecular level, we turned to magic angle spinning solid state NMR technique which is known to provide invaluable information on the Al, and thus proton, distribution in zeolites: we performed high-field magic angle spinning (MAS) 27 Al NMR experiments on both fresh and aged Pd/SSZ-13 samples [30][31][32][33][34]36] (Fig. 12).…”
Section: Insight Into the Structural Changes Of Fresh And Hta Pd/ssz-mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand the changes at the molecular level, we turned to magic angle spinning solid state NMR technique which is known to provide invaluable information on the Al, and thus proton, distribution in zeolites: we performed high-field magic angle spinning (MAS) 27 Al NMR experiments on both fresh and aged Pd/SSZ-13 samples [30][31][32][33][34]36] (Fig. 12).…”
Section: Insight Into the Structural Changes Of Fresh And Hta Pd/ssz-mentioning
confidence: 99%
“…Particles on the external surface are relatively sparse, confirming that only a fraction of Pd is removed from the pores, forming relatively large PdO agglomerates, in agreement with XRD. Additionally, HAADF-STEM images also reveal the formation of micro-and mesopores (defects) in the SSZ-13 crystals (circled in red, darker areas) due the steaming procedure [34].…”
Section: Insight Into the Structural Changes Of Fresh And Hta Pd/ssz-mentioning
confidence: 99%
“…Comparison of the pair distribution function (PDF) data for the fresh and aged 1 wt% Pd/SSZ-13 ( Figure 7) In order to understand the changes at the molecular level, we turned to magic angle spinning solid state NMR technique which is known to provide invaluable information on the Al, and thus proton, distribution in zeolites: we performed high-field magic angle spinning (MAS) 27 Al NMR experiments on both fresh and aged Pd/SSZ-13 samples [30][31][32][33][34]36] (Fig. 12).…”
Section: Xrd Studies Of Fresh and Hydrothermally Aged Pd/zeolite Modementioning
confidence: 99%
“…[12] The assignment of 15 NC P/MAS NMR signals has been made for pure imidazoles (mIM, eIM, and pIM) and ZIF-8 in Figure 3 and the Supporting Information, Figure S6. [14] Therefore,t he entirety of the zeolite crystals are functionalized and not just the pore mouth. While for ZIF-8, both of the Ni ni midazole were linked with Zn, only as ingle resonance at 204.5 ppm appeared.…”
mentioning
confidence: 99%
“…In HP-129 Xe NMR spectra (Supporting Information, Figure S7), the higher chemical shift of xenon were observed in ZnY-pIM and ZnZSM-5-pIM compared with ZnY and ZnZSM-5 indicated that xenon is adsorbed in ah ighly confined space,i no ther words,t he pore size of the zeolites become smaller after the decoration. [14] Therefore,t he entirety of the zeolite crystals are functionalized and not just the pore mouth. TEM images also indirectly suggested that the pore mouth also be functionalized (Supporting Information, Figure S8).…”
mentioning
confidence: 99%